THE EFFECT OF STORE AMBIENCE AND VALUE FOR MONEY ON CONSUMER PURCHASE INTENTION. CASE STUDY OF INDOMARET TOMOHON - Poluan, Farly .; Lapian, S.L.H.V. Joyce; Pandowo, Merinda . (Universitas Sam Ratulangi, 2018)
Abstract: In the competitive era, an attractive store ambiance is essential in encouraging customers to buy products. Meanwhile reasonable prices in a retail store induce customer satisfaction as well as build customer loyalty; hence value for money is important. So this research wants to analyze which of the two variables has a significant influence to customer purchase intention. Further, this research used Multiple Linear Regression as a research method. To archive the main purpose of this research, the sample size is 40 respondents. As a result of this research, both store ambience and value for money give significant influence to customer purchase intention. Hence, Indomaret Tomohon has to pay attention to their store ambience and value for money because the two factors has positive impact to customer purchase intention partially and simultaneously.Keywords: consumer purchase intention, store ambience, value for money